Studi Komparasi Model PBL dan PBL HYBRID berbasis STEAM terhadap Pemahaman Konsep Dasar-Dasar Listrik Siswa SMK Teknik Pembangkit Tenaga Listrik - Chusna, Chufadatul; Chisbiyah, Lismi Animatul (BRILIANT: Jurnal Riset dan Konseptual, 2024)
Comprehension of concepts plays a crucial role in the learning journey. The utilization of various learning models can influence students' grasp of these concepts. (1) It has been found that there is a correlation between student participation rates and concept understanding when using two different learning models, (2) it has been found that when using a Problem Based H learning model, classes with high and low activity levels showed the most significant difference in understanding concepts. The study involved students of the TPTL expertise program at Brantas Karangkates SMK. This is a real experimental research. The study sample consists of two groups. In this research, the data underwent analysis through descriptive methods, preliminary tests, and hypothesis testing utilizing SPSS statistical software. Findings indicated that the hybrid STEAM-based PBL learning model, the STEAM-based learning model, and the conventional STEAM learning model demonstrated varying levels of concept comprehension across highly active and moderately low active classes.